Health education using video recordings in a general practice waiting area: an evaluation. - Koperski, M (1989)
With the help of a patient participation group video recordings of health education programmes were shown in the waiting area of a health centre. Patients could choose whether or not to watch the programmes. When asked their views on the project 87% of patients responded positively, and 50% of those who watched could recall specific facts presented. There were no significant differences in age or sex between those who chose and chose not to watch the video recordings. However, unemployed patients and those in social classes 4 and 5 were significantly less likely to watch the programmes than those in social classes 1-3. The use of video recordings in both primary care and hospital waiting areas and the possible role of the health education authority as a central resource is discussed. This system could provide a useful means of extending health education, although further research is needed on the response of different social classes to different forms of health education.